A ciphertext‐policy attribute‐based proxy re‐encryption scheme for data sharing in public clouds. (13th October 2014) - Liang, Kaitai; Fang, Liming; Wong, Duncan S.; Susilo, Willy; Mustafee, Navonil; Bessis, Nik; Barolli, Leonard; Chen, Xiaofeng; Xhafa, Fatos
SUMMARY Ciphertext‐policy attribute‐based proxy re‐encryption (CP‐ABPRE) extends the traditional Proxy Re‐Encryption (PRE) by allowing a semi‐trusted proxy to transform a ciphertext under an access policy to another ciphertext with the same plaintext under a new access policy (i.e., attribute‐based re‐encryption). The proxy, however, learns nothing about the underlying plaintext. CP‐ABPRE has many real world applications, such as fine‐grained access control in cloud storage systems and medical records sharing among different hospitals. All the existing CP‐ABPRE schemes are leaving chosen‐ciphertext attack (CCA) security as an interesting open problem. This paper, for the first time, proposes a new CP‐ABPRE scheme to tackle the problem. The new scheme supports attribute‐based re‐encryption with any monotonic access structures. Despite being constructed in the random oracle model, our scheme can be proven CCA secure under the decisional q‐parallel bilinear Diffie–Hellman exponent assumption. Copyright © 2014 John Wiley & Sons, Ltd.